2020
DOI: 10.1093/mnras/staa371
|View full text |Cite
|
Sign up to set email alerts
|

The loss of the intracluster medium in globular clusters

Abstract: Stars in globular clusters (GCs) lose a non-negligible amount of mass during their post-main-sequence evolution. This material is then expected to build up a substantial intracluster medium (ICM) within the GC. However, the observed gas content in GCs is a couple of orders of magnitude below these expectations. Here, we follow the evolution of this stellar wind material through hydrodynamical simulations to attempt to reconcile theoretical predictions with observations. We test different mechanisms proposed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It has to be noted that in all our simulations we do not include ionizing feedback from SG stars which could lead to a steeper decrease of the SFR (Chantereau et al 2020). Massive stars belonging to the SG, if any, should contribute to heat up the ISM further, reducing the amount of gas eligible for star formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has to be noted that in all our simulations we do not include ionizing feedback from SG stars which could lead to a steeper decrease of the SFR (Chantereau et al 2020). Massive stars belonging to the SG, if any, should contribute to heat up the ISM further, reducing the amount of gas eligible for star formation.…”
Section: Discussionmentioning
confidence: 99%
“…The low density case is characterized by 𝜌 pg = 10 −24 g cm −3 while for the high density case we assume a gas density 10 times greater. Ours is one of the first "wind tunnel" experiment on cluster scale (Priestley et al 2011, C19), in which the effects of feedback are investigated in 3D (together with Chantereau et al 2020, who included photoionization). In our setup, the cluster is maintained fixed in its position and, at time 𝑡 inf , gas is allowed to flow into the computational box from one of the boundaries.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Typically, other than nuclear star clusters (Neumayer et al 2020), clusters (open clusters, YMCs or GCs) are not able to accrete significant amounts of gas from their surroundings. This is due to a combination of ram pressure and stellar feedback (winds, SNe, and photionisation), which act to expel the ejecta from stars within the cluster and stop accretion from the surroundings (e.g., Chantereau et al 2020). Additionally, most GCs have orbits away from the disk, both spatially and kinematically.…”
Section: Alternativementioning
confidence: 99%
“…This gas must be expelled in order to explain the lack of neutral ISM observed in Galactic GCs. Simulations by Chantereau et al (2020) found that both ram pressure stripping and ionisation is mandatory to explain the small amount of ionized gas in the core of GCs. We intend to investigate these channels of gas expulsion in future simulations of our Galactic GCs.…”
Section: G Concentration and Long Term Evolutionmentioning
confidence: 99%